Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Pendidikan Profesi Akuntansi Memilih Profesi Sebagai Akuntan Publik - Dewi, Pande Made Utariyani; Kresnandra, Anak Agung Ngurah Agung (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p12, 2019)
Professions and careers are needed to improve one's survival. This study aims to empirically examine the effect of financial awards, professional training and work environment on the interest of Accounting Professional Education students to choose a profession as public accountant. Samples were obtained by nonprobability sampling method with saturated sampling techniques. Respondents were students of Accounting Professional Education at Udayana University in 2017 with 30 students. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis show that financial rewards have a positive effect on the interest of accounting profession education students to choose a profession as a public accountant. Professional training has a positive effect on the interest of accounting profession education students in choosing a profession as a public accountant. The work environment has a positive effect on the interest of accounting profession education students in choosing a profession as a public accountant. Keywords : Financial Awards; Professional Training; Work Environment.